Middle Eastern and African Perspectives on the Development of Public Relations Other Voices - Watson, T.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
The National Perspectives on the Development of Public Relations: Other Voices series is the first to offer an authentic world-wide view of the history of public relations. It will feature six books, five of which will cover continental and regional groups. This third book in the series focuses on the Middle East and Africa.
Keywords: International business enterprises; Leadership; Marketing; Public relations; Development economics; International economics; International Business; Business Strategy/Leadership.; Marketing; Corporate Communication/Public Relations; Development Economics; International Economics